Haemostasis Factors in Angina Pectoris; Relation to Gender, Age and Acute-phase Reaction - Haverkate, F; Thompson, S G; Duckert, F (Thrombosis and Haemostasis, 1995)
The ECAT Angina Pectoris Study is a European multicentre study with the aim of investigating the pathogenetic and predictive role of haemostatic factors in the progression of coronary heart disease. It is the largest study performed up to now with regard to both the number of patients with angina pectoris (n = 3043) and the number of haemostasis assays (n = 23) included.The present paper presents baseline cross-sectional data with particular reference to the relationship of haemostatic factors with each other and with the coronary risk factors age, gender and acute-phase reaction (1). Two clusters of haemostatic factors could be distinguished in which each variable was correlated (P < 0.001) to every other variable: (a) Eight fibrinolysis assays including t-PA, PAI-1 and euglo- bulin clot lysis time (ECLT), for which PAI-1 appeared to be the dominating factor; (b) antithrombin III, protein C, α2-antiplasmin and plasminogen, the interdependence of which has no obvious explanation. (2). Twelve out of the 23 haemostasis assays were associated (P < 0.01) with age. Except for α2-antiplasmin, these relationships indicated an increased tendency to thrombosis with increasing age. (3). Gender differences found in 14 haemostasis parameters do not indicate a consistent difference in the tendency to thrombosis between men and women. Eight haemostasis parameters were on average higher in female than in male patients in the age group over 50 years. (4). C-reactive protein, an acute-phase reactant, was positively correlated (P < 0.001) with fibrinogen, factor VIIIc, von Willebrand factor, the fibrinolysis assays t-PA, PAI-1, ECLT and plasminogen. These parameters are therefore potential markers of an ongoing, low-grade inflammatory response in patients with atherosclerosis and, as most of them have been reported as cardiovascular risk markers, they may be involved in the pathogenesis of the disease as a link in the relation between inflammation and arterial thrombosis.